ST2 and REG3α as Predictive Biomarkers After Haploidentical Stem Cell Transplantation Using Post-transplantation High-Dose Cyclophosphamide - Solán, Laura; Kwon, Mi; Carbonell, Diego; Dorado, Nieves; Balsalobre, Pascual; Serrano, David; Chicano-Lavilla, María; Anguita, Javier; Gayoso, Jorge; Díez-Martín, José Luis; Martínez-Laperche, Carolina; Buño, Ismael (Frontiers in Immunology, 2019)
Allogenic hematopoietic stem cell transplantation (allo-HSCT) is a curative procedure for several hematological malignancies. Haploidentical HSCT (haplo-HSCT) using high-dose post-transplantation cyclophosphamide (PTCy) makes transplantation possible for patients with no HLA-matched sibling donor. However, this treatment can cause complications, mainly infection, graft-vs.-host disease (GVHD), and conditioning-related toxicity. In recent years, different biomarkers in the form of tissue-specific proteins have been investigated; these may help us to predict complications of allo-HSCT. In this study we explored two such biomarkers, suppression of tumorigenicity 2 (ST2) and regenerating islet-derived 3α (REG3α), in the largest series reported of T cell–replete haplo-HSCT with PTCy. Plasma samples drawn from 87 patients at days +15 and +30 were analyzed. ST2 and REG3α levels at day +15 were not associated with post-transplant complications. ST2 levels at day +30 were higher in patients with grade II-IV acute GVHD, mainly those who received reduced intensity conditioning (RIC; median 2,503 vs. 1,830 ng/ml; p = 0.04). Of note, patients with higher plasma ST2 levels at day +30 also presented a higher incidence of non-relapse mortality (HR, 7.9; p = 0.004) and lower 2-year overall survival (25 vs. 44 months; p = 0.02) than patients with lower levels. Patients with REG3α levels higher than 1,989 pg/ml at day +30 presented a higher incidence of acute gastrointestinal GVHD in the whole cohort (HR, 8.37; p = 0.003) and in the RIC cohort (HR 6.59; p = 0.01). These data suggest that measurement of ST2 and REG3α might be useful for the prognosis and prediction of complications in patients undergoing haplo-HSCT with PTCy.